The consistency of the World Anti-Doping Code’s whereabouts requirements and the rights guaranteed for the athletes under EU law - Alanko, Ella (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis will address the consistencies and inconsistencies of the EU legislation and the whereabouts requirements of the World Anti-Doping Agency. The whereabouts requirements are regulated in the World Anti-Doping Code and in its annexed International Standards. The whereabouts requirements can be divided into the requirement to submit personal information and to the requirement of filing. According to the International Standard for Testing and Investigations, an athlete, who is placed in a Registered Testing Pool, must for the upcoming quarter for each day file one specific 60-minute time slot and a specific location and to be accessible for Testing during that time at that place. The EU Member States are bound by the Word-Anti Doping Code as they all have ratified the International Convention Against Doping in Sports by the UNESCO. The legal basis for the EU’s sports competence has been regulated in Article 6 and 165 TFEU since the adoption of the Lisbon Treaty. However, even before the formal legal basis, the European Court of Justice has been a dynamic interpreter of EU sports competence and has greatly impacted the sports regulation within its jurisdiction through judgments such as Walrave and Koch, Bosman and Meca-Medina and Majcen. In my thesis, I argue that EU can now address the World-Anti Doping Code’s whereabouts requirements in the light of EU law and adjudicate the consistency of the two very different legal systems, one a consortium of the Member States and the other a global private foundation. The relationship of the EU and the World Anti-Doping Code as well as the relationship of the European Court of Justice and The Court of Arbitration for Sports will be addressed. Despite the arbitration clauses in the World Anti-Doping Code, issues related to the Code’s content can be submitted by EU athletes to the European Court of Justice. The thesis will concentrate on the consistency of the whereabouts requirements and the EU legislation, especially in the light of the Working Time Directive and the Data Protection legislation. The core of the thesis is to shed light on any problematic parts in order to proactively avoid the collision of the two systems.